THE DISRUPTION AND TRANSFORMATION OF SOCIAL STUDIES EDUCATION IN INDONESIA: CHALLENGES, OPPORTUNITIES, AND ADAPTIVE STRATEGIES IN THE DIGITAL ERA - Meila Yufriana Devi; Aim Abdulkarim; Asep (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The era of disruption has brought fundamental changes to the education system, including Social Studies learning in Indonesia. The rapid development of digital technology, increasingly complex social dynamics, and the demand for twenty-first-century competencies have positioned Social Studies as a strategic subject in fostering learners who are critical, adaptive, reflective, and socially responsible. This study aims to analyze the transformation of Social Studies learning in Indonesia in the digital era by highlighting instructional strategies, teacher readiness, curriculum adaptation, technology integration, and educational policy support. This research employs a literature review approach by examining various relevant scholarly publications published between 2022 and 2025. The findings indicate that the era of disruption has encouraged Social Studies learning to become more interactive, student-centered, contextual, project-based, and integrated with digital literacy. However, this transformation still faces several challenges, including infrastructure disparities, uneven teacher digital competencies, resistance to pedagogical change, and limited access to technology across different regions. On the other hand, the Merdeka Curriculum provides significant opportunities to strengthen Social Studies learning so that it becomes more flexible, relevant to both local and global contexts, and oriented toward the development of twenty-first-century competencies. This study confirms that strengthening Social Studies learning in the era of disruption requires synergy among teacher capacity building, pedagogical innovation, equitable digital infrastructure, and adaptive as well as inclusive education policies in order for learning transformation to take place effectively and sustainably.